Russia at the Turn of the World Economy - D. E. Matreshina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The purpose of this study is to determine and substantiate the importance of deepening cooperation between the Russian Federation and the countries of the Asian region in modern conditions. The work emphasizes and substantiates the importance of the development of integration processes in the formation of a strategy for international cooperation of states in the context of global socio-economic and political restructuring. The general world tendencies influencing the Russian economy in the conditions of a gradual transition to a new world economic order are given. The article examines the policy pursued by the state that can influence its place within the framework of the new integral world economic order. The paper describes the transformation and structure of relations between the member states of the Eurasian Economic Union (EAEU) with the countries of the Shanghai Cooperation Organization (SCO) and the Association of Southeast Asian Nations (ASEAN) in the context of the emerging concept of the Greater Eurasian Partnership and the change in the world economic order.When preparing the work, first of all, we used a logical, factorial, statistical analysis, synthesis, a systematic approach.The scientific novelty of the work consists in defining and describing Russia’s potential within the framework of the transition to a new world economic order, taking into account a combination of factors, namely: its position in the Eurasian Economic Union, the implementation of the Strategic Directions for the Development of Eurasian Economic Integration until 2025, the development of cooperation with the SCO and ASEAN states, as well as conjugation of the EAEU and the One Belt, One Road project.